Gender-based differences of intraoperative transfusion during open surgery for descending thoracic and abdominal aortic aneurysms: a retrospective single-center cohort study - Jianfeng Gao; Ruxuan Wang; Fangda Li; Rong Zeng; Yuexin Chen; Yuehong Zheng (BMC Surgery)
Abstract Background Several studies have reported gender-based differences in prognosis following open surgery repair (OSR) and endovascular therapy for treating aortic aneurysms. However, the blood transfusion rates for both gender and the predictors of intraoperative transfusion during OSR for Descending Thoracic and Abdominal Aortic Aneurysms (DTAA) remain uncertain. Methods Data of Patients with DTAA who underwent OSR at our center between August 2002 and December 2021 were retrospectively collected. Specific aneurysms and preoperative anemia were excluded from the study. Transfusion of blood products was recorded. Logistic regression analyses were conducted to identify the factors significantly related to transfusion. An adjusted analysis of the association between gender and red blood cell (RBC) transfusion was performed. Results A total of 82 patients were included, of whom 23 were female. Forty-six DTAAs received intraoperative RBC transfusions. The transfusion rates for male and female were 45.8% and 82.6%, respectively. Preoperative hemoglobin concentration (Hb) was similar between the transfusion and no-transfusion cohorts. Female gender, thoracoabdominal aortic aneurysm, increased procedure duration, blood loss, and urine volume were associated with higher intraoperative transfusion rates. Female gender was identified as an independent predictor (odds ratio [OR], 5.24; P = 0.034). Preoperative Hb, statin use, blood loss, and urine volume were significantly different between gender. After adjusting for these four factors, an association between female gender and RBC transfusion was also found (OR, 6.63; P = 0.037). According to the receiver operator characteristic curve (ROC), increased age (cutoff = 66 years, area under curve [AUC] = 0.81, P = 0.044) and longer procedure duration (cutoff = 245 min, AUC = 0.84, P = 0.021) were found to have significant predictive value for intraoperative transfusion in women. Conclusion Women with DTAA may have a higher requirement for intraoperative RBC transfusion. Therefore, women appear to require more comprehensive RBC preparation plans for elective OSR.